Asuhan Keperawatan Keluarga Tahap Perkembangan Dewasa Muda dengan Intervensi Senam Kaki terhadap Penurunan Glukosa Darah Lansia - Chaerunnisa Eka Sania; Rina Puspita Sari; Hasan Basri (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The young adult family is the stage that begins when the first child decides to leave the parental home. The tasks of family development at this stage include helping and preparing children to be independent, maintaining harmony with a partner, expanding the nuclear family into a large family, preparing to take care of a large family entering old age, and providing examples to children regarding a positive home environment. According to most people, this stage is a stage full of stressors and is prone to suffering from diseases, one of which is diabetes mellitus. Based on the results of the assessment of the family of Mr. This family type is a nuclear family with a young adult stage of development where the child is 19 years old. In the family of Mr. S, it was found that Mr. S suffered from diabetes mellitus since 1 year ago, Mr. S likes to consume sweet foods, Mr. S was also lazy to exercise because his legs hurt, Mr. S also did not know how to reduce diabetes mellitus other than taking medication given by the doctor. The purpose of this study is to describe foot exercises in families who experience diabetes mellitus to determine the effectiveness of foot exercises on lowering blood glucose. This research method is a case study conducted with foot exercise therapy for 6 meetings with 10-15 minutes, foot exercise treatment intervention and diabetes mellitus education. The results of this study are that post foot gymnastics therapy Mr. S experienced different results, namely before being done. S experienced different results, namely before foot gymnastics in patients with diabetes mellitus with GDS 249 mg / dL then after foot gymnastics became GDS 150 mg.dL which was carried out for 6 days of meetings with 10-15 minutes. The conclusion of this study is that while providing foot gymnastics techniques effectively reduce glucose in the blood felt by Mr. S so that it decreased by 99 mg / dL. S so that it decreased by 99 mg/dL.